2006
DOI: 10.1080/17470910600670603
|View full text |Cite
|
Sign up to set email alerts
|

Politics on the brain: An fMRI investigation

Abstract: We assessed political attitudes using the Implicit Association Test (IAT) in which participants were presented faces and names of well-known Democrat and Republican politicians along with positive and negative words while undergoing functional MRI. We found a significant behavioral IAT effect for the face, but not the name, condition. The fMRI face condition results indicated that ventromedial and anterior prefrontal cortices were activated during political attitude inducement. Amygdala and fusiform gyrus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 67 publications
(73 reference statements)
6
69
0
2
Order By: Relevance
“…In other words, this study will be the first to disentangle two distinct processes that contribute to prejudiceingroup favoritism (positive associations) and outgroup negativity (negative associations). Further, application of the Quad model will also refine our understanding of the frontal lobe activations found in previous research on the IAT (e.g., Chee et al, 2000;Luo et al, 2006;Knutson et al, 2006;2007;Richeson et al, 2003) by generating independent estimates of two distinct controlled processes (D, OB) that can be related to neural activity.…”
Section: Overview Of the Present Studymentioning
confidence: 78%
See 3 more Smart Citations
“…In other words, this study will be the first to disentangle two distinct processes that contribute to prejudiceingroup favoritism (positive associations) and outgroup negativity (negative associations). Further, application of the Quad model will also refine our understanding of the frontal lobe activations found in previous research on the IAT (e.g., Chee et al, 2000;Luo et al, 2006;Knutson et al, 2006;2007;Richeson et al, 2003) by generating independent estimates of two distinct controlled processes (D, OB) that can be related to neural activity.…”
Section: Overview Of the Present Studymentioning
confidence: 78%
“…Therefore, fMRI studies of IAT performance typically compare neural activity in the Incongruent condition to the Congruent condition. These studies have found neural regions associated with controlled processes to be more active in Incongruent than Congruent conditions (middle frontal gyrus: Knutson et al, 2007;ventrolateral prefrontal cortex and anterior cingulate: Luo et al, 2006; left inferior frontal gyrus: Knutson et al, 2006;Chee et al, (2000) did not design their study to permit a direct comparison between the Incongruent and Congruent conditions). However, although the discrepancy in reaction time between the Incongruent and Congruent conditions is the basis for behaviorally measuring implicit bias, it is unlikely that neural activity associated with this comparison measures automatic components of attitudes in an fMRI environment.…”
Section: Previous Neuroimaging Research Using the Iatmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous fMRI studies have examined the congruency of affective associations towards social targets (Harris & Fiske, 2010;Knutson, Wood, Spampinato, & Grafman, 2006;Westen, Blagov, Harenski, Kilts, & Hamann, 2006) and, using electroencephalography (EEG), both regulation of racial bias and perceived violations of social expectations have been investigated (Amodio, Harmon-Jones, Devine, Curtin, Hartley, & Covert, 2004;Amodio, Kubota, Harmon-Jones, & Devine, 2006). Furthermore, with the help of EEG, the neural operations underlying the processing of words or sentences that are either congruent or incongruent in terms of gender stereotypes have been studied (Osterhout, Bersick, & McLaughlin, 1997;White, Crites, Taylor, & Corral, 2009).…”
mentioning
confidence: 99%